2011
DOI: 10.1017/s1355617711001524
|View full text |Cite
|
Sign up to set email alerts
|

Specific Measures of Executive Function Predict Cognitive Decline in Older Adults

Abstract: Decline in executive function has been noted in the prodromal stage of Alzheimer’s disease (AD) and may presage more global cognitive declines. In this prospective longitudinal study, five measures of executive function were used to predict subsequent global cognitive decline in initially nondemented older adults. Of 71 participants, 15 demonstrated significant decline over a 1-year period on the Dementia Rating Scale (Mattis, 1988) and the remaining participants remained stable. In the year before decline, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
81
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 47 publications
8
81
0
2
Order By: Relevance
“…A combination of memory and executive function measured by RT has been reported as the strongest predictor of progression to Alzheimer's disease [23]. Recently, the performance on specific executive function, such as inhibition, has been proved to be useful in distinguishing MCI subjects from healthy adults [24]. …”
Section: Discussionmentioning
confidence: 99%
“…A combination of memory and executive function measured by RT has been reported as the strongest predictor of progression to Alzheimer's disease [23]. Recently, the performance on specific executive function, such as inhibition, has been proved to be useful in distinguishing MCI subjects from healthy adults [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Of the other specific cognitive domains, only executive function had a significant effect size in the full independent cohorts analysis. Studies not using biomarkers of amyloid have suggested that measures of executive function may predict subsequent decline toward dementia, 29 although changes in executive function may occur later, relative to memory decline, in preclinical AD. 30 Global cognitive function had an effect size approximately as large as episodic memory across analyses and so may provide an important indicator of the earliest influences of amyloid on cognition.…”
mentioning
confidence: 99%
“…There are international studies of children samples (Hurks et al, 2010;Nieto, Galtier, Barroso, & Espinosa, 2008;Sauzéon et al, 2004;Tallberg, et al, 2011) and adult samples (Clark et al, 2012;Raboutet et al, 2010;Troyer, 2000;Troyer et al, 1997) with typical development. There are studies using samples of neurological patients with Parkinson's disease (Anzak et al, 2011;), Alzheimer's disease (Troyer, Moscovitch, Winocur, Leach et al, 1998;Zhao, Guo, & Hong, 2013), Huntington's disease (Rich, Troyer, Bylsma, & Brandt, 1999), stroke (Vivas & Naveira, 2010), and brain lesions without specific causes (Okruszek, Rutkowska, & Wilinska, 2013;Stuss, et al, 1998;Tröster et al, 1998;.…”
mentioning
confidence: 99%